KONSEP PENDIDIKAN HASYIM ASY’ARI; TIPOLOGI DAN RELEVANSINYA TERHADAP PARADIGMA PENDIDIKAN INDONESIA EMAS 2045 - Bahri, Rosidi; Fuad, Ah. Zakki; Bakar, M. Yunus Abu (Reflektika, 2024)
AbstractHasyim Asy'ari is better known as a cleric who transformed Islamic boarding school education, as well as being a fighter. Hasyim Asy'ari turned Tebuireng into a model Islamic boarding school for Islamic boarding schools throughout Indonesia. By using relevant literature data from the book Adab al-Alim wa al-Muta'allim by Hasyim Asy'ari, this research uses library research by collecting information through documentary methods. In the book Directions for Competency of the Indonesian Generation Towards a Golden Indonesia 2045 prepared by the National Education Standards Agency (BNSP), Indonesia will celebrate its 100th anniversary of independence in 2045. Indonesia will experience a golden age at that time. Education needs to be organized as a "Garden that Excites", "Garden that Grows", and "Garden that Strengthens", in accordance with the ideals of Ki Hajar Dewantara. Because there are no castes based on intelligence (ranking), all students feel safe and comfortable in the "Education Park". Each student feels valued for their individuality and uniqueness in the park. It is in gardens like this that humans mature into civilized creatures. His contribution of thought, whether in the form of works, or his work in establishing Islamic boarding schools and the Nahdlatul Ulama organization has proven his work and is valid evidence to attribute to him the figure of Indonesian Islamic education.  As part of a conservative traditional education figure, Hasyim Asy'ari's contribution to educational thought was enormous to the journey of education, especially Islamic boarding school education. Hasyim Asy'ari's thoughts are very relevant to national education issues across eras and are suitable to be adopted in preparing Indonesia's golden generation in the future.